Reconfigurable computing the theory and practice of FPGA-based computation - Hauck, Scott; DeHon, André (Morgan Kaufmann series in systems on silicon., 2008)
The main characteristic of Reconfigurable Computing is the presence of hardware that can be reconfigured to implement specific functionality more suitable for specially tailored hardware than on a simple uniprocessor. Reconfigurable computing systems join microprocessors and programmable hardware in order to take advantage of the combined strengths of hardware and software and have been used in applications ranging from embedded systems to high performance computing. Many of the fundamental theories have been identified and used by the Hardware/Software Co-Design research field. Although the same background ideas are shared in both areas, they have different goals and use different approaches. This book is intended as an introduction to the entire range of issues important to reconfigurable computing, using FPGAs as the context, or computing vehicles to implement this powerful technology. It will take a reader with a background in the basics of digital design and software programming and provide them with the knowledge needed to be an effective designer or researcher in this rapidly evolving field. Treatment of FPGAs as computing vehicles rather than glue-logic or ASIC substitutes Views of FPGA programming beyond Verilog/VHDL Broad set of case studies demonstrating how to use FPGAs in novel and efficient ways.